2023
DOI: 10.37479/jebe.v1i2.18046
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Pelayanan Terhadap Keputusan Pembelian

Abstract: The purpose of this research was to determine to what extent service quality affected purchase decisions at Cv. Mufidah, Gorontalo City.” This research employed a quantitative approach using a quantitative correlational method with a sample size of 30 consumers. Besiders, the data collection techniques used in this research were interviews, questionnaires, and documentation, while the data analysis technique was simple regression analysis. The research finding denoted that there was a positive and significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This means that H1 is accepted, indicating that service quality has a positive and significant influence on students' decisions to choose Universitas Mikroskil. This research is consistent with previous studies that found a positive and significant influence of service quality on buyer decisions (Novita et al, 2023). stating that service quality influences students' decisions.…”
Section: Discussionsupporting
confidence: 93%
“…This means that H1 is accepted, indicating that service quality has a positive and significant influence on students' decisions to choose Universitas Mikroskil. This research is consistent with previous studies that found a positive and significant influence of service quality on buyer decisions (Novita et al, 2023). stating that service quality influences students' decisions.…”
Section: Discussionsupporting
confidence: 93%